Radiographic and Histopathologic Analysis on Osteoarthritis Rat Model Treated with Essential Oils of Rosmarinus officinalis and Populus alba - Hamza Belkhodja , Boumediene Meddah, Aicha Meddah TirTouil, Khaled Slimani, Abdenacer Tou (Tabriz University of Medical Sciences, 2017)
Background: The plants represent an important source of various chemical structures known for their therapeutic activities in folk medicine. Our study aimed to exploit natural bioactive components from well-known medicinal plants "Rosmarinus officinalis and Populus alba". Methods: The study of acute toxicity of essential oils of Rosemary and White poplar was carried out on Wistar rats. Then, the effect of these essential oils was studied in the treatment of experimental models induced by knee osteoarthritis. A radiographic and Histologic analysis was carried out to monitor the efficiency of essential oil. The choice of the model of osteoarthritis turned to unilateral intra-articular injection of a mono-iodo acetic acid. Results: The results revealed that the action of the essential oil showed a significant decrease in the Mankin score compared to the group of untreated rats. Conclusion: The essential oils of R. officinalis, P. alba presented an protective effect against osteoarthritis with difference degrees.